Disulfiram-alcohol reaction in 49 year old patient - Krystian Lech Ciechański; Jędrzej Tkaczyk; Klaudia Brożyna; Aleksandra Kędziora; Katarzyna Baltaziak; Michał Tchórz (Kazimierz Wielki University, 2018)
Alcoholism is a disease in which person lose control over the amount of consumed alcohol. The problem of alcohol abuse in Poland concerns about 9% of the population. One of the treatment methods is disulfiram therapy, which is associated with the risk of disulfiram-alcohol reaction. Due to many negative reports of side effects and questionable efficacy, this drug is nowadays rare used. We present a case of a patient who had a disulfiram reaction due to alcohol consumption during disulfiram therapy.